2016
DOI: 10.1177/2158244015627672
|View full text |Cite
|
Sign up to set email alerts
|

Integration of Religion and Spirituality With Social Work Practice in Disability Issues

Abstract: This case study examines the integration of religion and spirituality (RS) into disability issues from the perspective of social work in Sri Lanka. Participant observation was applied in the model administrative division of the national community-based rehabilitation (CBR) program in Anuradhapura from February 2013 to January 2015. Theravada Buddhists constitute more than 99% of the population in the area studied. The participation opportunities included group activities, home visits to disabled people, and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 17 publications
1
8
0
1
Order By: Relevance
“…Nonetheless, most of them, even those who did not participate in the community regularly, reported taking part in religious activities outside the home. These findings support the observations of field studies in another part of rural Sri Lanka, which revealed a lifestyle without any activities (Higashida, Kumara, and Nakashima 2016) and the importance of religious participation for disabled people (Higashida 2016), although the difference between religious and other community activities from a local viewpoint would also need to be considered in the context of cultural and religious norms.…”
Section: The Association Between Socioeconomic Factors and Community supporting
confidence: 87%
“…Nonetheless, most of them, even those who did not participate in the community regularly, reported taking part in religious activities outside the home. These findings support the observations of field studies in another part of rural Sri Lanka, which revealed a lifestyle without any activities (Higashida, Kumara, and Nakashima 2016) and the importance of religious participation for disabled people (Higashida 2016), although the difference between religious and other community activities from a local viewpoint would also need to be considered in the context of cultural and religious norms.…”
Section: The Association Between Socioeconomic Factors and Community supporting
confidence: 87%
“…Conceptually, spirituality can meet social goals of rehabilitation counseling by cultivating a relational consciousness (i.e., positive and enabling relationships with self and others; Conner, 2010; Picard, 2009; Reinders, 2008; Skar, Folkestad, Smedal, & Grytten, 2014) and deconstructing notions of disability by transcending the ability/disability binaries (Boswell, Knight, & Hamer, 2001; Yong, 2007). This then extends to vocational goals in terms of negotiating for equal access and opportunities, equity, and repositioned vocational goals (Higashida, 2016; Muscott & Melloy, 2001; Selway & Ashman, 1998).…”
Section: Methodsmentioning
confidence: 99%
“…With respect to rehabilitation counseling, attention is now being paid to training practitioners to build on clients’ religion and spirituality (Higashida, 2016; Oxhandler & Pargament, 2014). This makes a case for understanding whether and how professionals/practitioners view the role of spirituality in rehabilitation counseling of persons with disability.…”
Section: Introductionmentioning
confidence: 99%
“…Further to this, Canda and Furman (2010) point out that, 'by considering the religious and spiritual facets of clients' lives, we may identify strengths and resources that are important for coping, resilience, and optimal development' (p. 5). Emphatically, certain spiritual or religious practices have been documented to improve health such as; a decreased risk of stroke, lower blood pressure, engaging in healthier habits such as not drinking and smoking, reducing mental health and suicidal ideation, lower depression and anxiety levels (Davidson, 2003;Weisman de Mamani et al, 2010) and increased feelings of hope, optimism, and positivity (Higashida, 2016). Religious and spiritual practices have also been shown to increase a sense of community and social support for vulnerable populations (Jacobs, 2010).…”
Section: Mainstreaming Spirituality In Contemporary Social Work Practicementioning
confidence: 99%